2020
DOI: 10.5808/gi.2020.18.3.e28
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and functional annotation of a hypothetical protein (SCO0618) of Streptomyces coelicolor A3(2)

Abstract: Streptomyces coelicolor is a gram-positive soil bacterium which is well known for the production of several antibiotics used in various biotechnological applications. But numerous proteins from its genome are considered hypothetical proteins. Therefore, the present study aimed to reveal the functions of a hypothetical protein from the genome of S. coelicolor. Several bioinformatics tools were employed to predict the structure and function of this protein. Sequence similarity was searched through the available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…However, Streptomyces genomes still contain large numbers of functionally unknown TCS-coding genes [ 33 , 37 ]. Moreover, Streptomyces genomes also contain numerous HP genes with unknown functions [ 38 , 39 ]. For example, there are 3694 (47% of the total annotated genes) HP genes in S. coelicolor and 3604 (36% of the total genes) in S. bingchenggensis [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Streptomyces genomes still contain large numbers of functionally unknown TCS-coding genes [ 33 , 37 ]. Moreover, Streptomyces genomes also contain numerous HP genes with unknown functions [ 38 , 39 ]. For example, there are 3694 (47% of the total annotated genes) HP genes in S. coelicolor and 3604 (36% of the total genes) in S. bingchenggensis [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proteins were regarded as good vaccine candidates only when the transmembrane helices were less than the threshold, as such proteins can be easily handled in experimental studies. The selected proteins were further processed in downward analysis [55].…”
Section: Transmembrane Helicesmentioning
confidence: 99%
“…With the advancement of Computational Biology, it has become easier to analyze hypothetical proteins using bioinformatics tools that provide various advantages like the determination of 3D structural conformation, identification of new domains and motifs, assessment of new cascades and pathways, phylogenetic profiling, and functional annotation [ 11 ]. A recent study showed that the annotated hypothetical protein is linked with hydrolase activity which might be of great interest to further research in bacterial genetics [ 12 ].…”
Section: Introductionmentioning
confidence: 99%